Minilaparotomy interval - Pinedo, Adolfo (2015)
Minilaparotomy interval is a surgical procedure that involves less suprapública abdominal incision of 5 cm., Usually 3 cm., Through which reach the peritoneal cavity to locate, display and perform tubal ligation. An instrument known as uterine elevator (Ramathibodi) inserted into the uterus helps with proper shift the location of both tubes.